2017
DOI: 10.1111/hepr.12912
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting overall response and overall survival in hepatocellular carcinoma patients undergoing balloon‐occluded transcatheter arterial chemoembolization: A retrospective cohort study

Abstract: Balloon-occluded transcatheter arterial chemoembolization may exert a good antitumor effect and result in good overall survival in select hepatocellular carcinoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 26 publications
1
18
0
3
Order By: Relevance
“…Transcatheter arterial chemoembolization (TACE) is a standard therapy for unresectable HCC, especially for patients with BCLC B . Several studies have shown that TACE significantly improves patient survival compared to the best supportive care and can prolong survival in patients with multiple HCC tumors and no macrovascular invasion . However, long‐term prognosis of patients treated with TACE alone is unsatisfactory and overall survival at 3 years remains low (<30%) for intermediate HCC patients because of poor local control of HCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcatheter arterial chemoembolization (TACE) is a standard therapy for unresectable HCC, especially for patients with BCLC B . Several studies have shown that TACE significantly improves patient survival compared to the best supportive care and can prolong survival in patients with multiple HCC tumors and no macrovascular invasion . However, long‐term prognosis of patients treated with TACE alone is unsatisfactory and overall survival at 3 years remains low (<30%) for intermediate HCC patients because of poor local control of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…8 Several studies have shown that TACE significantly improves patient survival compared to the best supportive care and can prolong survival in patients with multiple HCC tumors and no macrovascular invasion. [9][10][11][12] However, long-term prognosis of patients treated with TACE alone is unsatisfactory 13 and overall survival at 3 years remains low (<30%) for intermediate HCC patients because of poor local control of HCC. Radiofrequency ablation (RFA) is the main treatment method for patients with inoperable and small HCCs.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, B-TACE induced denser lipiodol emulsion accumulation and a good local control effect in the HCC nodules [11,17]. Recent studies reported favorable predictors affecting the local control effect after B-TACE as follows: portal vein visualization during B-TACE, tumor on the subcapsular portion, successful subsegmental feeding artery embolization [23], single HCC, AFP level < 20 ng/ml [18], high CT value immediately after B-TACE [24], and enhanced tumor stain on CT during hepatic angiography under balloon occlusion [25]. In the present study, balloon increase, absence of PVTT, absence of previous C-TACE, and maximum tumor size smaller than 2 cm were significantly associated with progression-free survival on the univariate analysis, but none were significantly associated with progression-free survival on the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Irie et al reported that the median survival time was 3.5 years in the 28 patients with 1 or 2 HCC nodules treated using B-TACE with doxorubicin hydrochloride and mitomycin C [26]. Hatanaka et al reported that the median survival time was 902 days in 66 patients treated using B-TACE with miriplatin [18]. In the present study, the 1-, 2-, and 3-year survival rates were 89.2%, 67.3%, and 60.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation